Metaloproteinase de tripanosomatídeos: avaliação de potenciais inibidores como ferramenta para desenvolvimento de fármacos - Moreno, Cláudia Jassica Gonçalves (2020)
Antiparasitic therapy for the treatment and control of neglected tropical diseases caused by trypanosomatids is limited due to their high toxicity and low drug efficacy. Currently there is no available vaccine for control of human diseases. This study had a multidisciplinary and cross-sectional character whose main objective was the biological and biochemical characterization of trypanosomatids metalloproteases (gp63) with emphasis on the research of news potential compounds capable of inhibition protein activity. Thus, the enzymatic activity, metalloprotease identification and hemolytic capacity of different Trypanosomatids crude extracts were evaluated. After that, in silico and in vitro analyzes were performed with the potential news gp63 inhibitors. Through, zymography assays the proteolytic profile was visualized from Leishmania spp. crude extract proteins on gelatin and casein substrate. Trypanosoma cruzi exhibited a proteolytic pattern consistent with the profile previous described for cruzipain, a cysteine protease. In collaboration with the Chemistry Institute of UFRN, a fluorescent assay dependent on Zn2+ ion coordination was developed. The results showed the strong coordination of compound L1 and Zn (II) present in the crude extract of L. amazonensis. In addition, biological assays demonstrated complement system mediated hemolytic activity in the presence of trypanosomatids extract. In silico approach demonstrated molecular anchoring with favorable energies for the interaction between the ligands tested: L1> DETC> Doxycycline> 4TERP37. Besides, a similar result was observed in the calculation of the quantum final energy balance. In vitro validation of the compounds showed that L1 significantly decreases the viability of the promastigote’s forms of L. amazonensis (IC50 of 1.24 µM). L1 compound, not described so far, induced promastigotes death by necrosis process and structural analysis, revealed that membrane damage, small holes in the membrane, as well as cell content. Differently, L1 showed a high selectivity index over cell lines, 3T3 and RAW. Together, the results showed a potential leishmaniocidal effect of L1 against L. amazonensis, the etiologic agent of diffuse leishmaniasis, the only clinical form that currently doesn´t exist treatment. In parallel to this study, Trypanosoma brucei surface variable protein (VSG) analysis was performed. It was found that matrix metalloproteases (MMPs) recognize parasite VSGs molecules. Although, both results represent a contribution to the future approach on development therapeutic in diseases caused by Trypanosomatids. However, more further studies will allow to attest the presents results.